1986
DOI: 10.1007/bf00282073
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphism related to the idiopathic hemochromatosis gene: evidence in a recombinant family

Abstract: The metabolic error involved in idiopathic hemochromatosis, as well as the underlying genetic defect remain unknown. It has, however, been recently shown that this genetic lesion occurs at a locus linked to the major histocompatibility complex, probably close to the HLA-A locus, and that the disease is recessively transmitted. Therefore, in a family where one subject has idiopathic hemochromatosis his HLA-identical siblings should also be affected. We present here the restriction polymorphism with two MHC clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
1996
1996

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This led to the conclusion that the gene was located closer to the A than to the B locus. It remains unclear whether the gene for hemochromatosis maps between the A and B loci, as suggested by Edwards et al [14], or telomeric to the A locus [15]. The lat ter hypothesis is supported by a recent report by Jazwinska et al [16] who employed micro satellites (short tandem repeated sequences) identified on the short arm of chromosome 6 as a tool to localize the hemochromatosis gene.…”
Section: Geneticsmentioning
confidence: 99%
“…This led to the conclusion that the gene was located closer to the A than to the B locus. It remains unclear whether the gene for hemochromatosis maps between the A and B loci, as suggested by Edwards et al [14], or telomeric to the A locus [15]. The lat ter hypothesis is supported by a recent report by Jazwinska et al [16] who employed micro satellites (short tandem repeated sequences) identified on the short arm of chromosome 6 as a tool to localize the hemochromatosis gene.…”
Section: Geneticsmentioning
confidence: 99%
“…Such studies have included restriction enzyme studies of DNA from affected families seeking restriction fragment length polymorphisms which could provide markers for the disease. No defini· tive results are so far available despite some early promise (25).…”
Section: Geneticsmentioning
confidence: 99%